Fluid therapy and pulmonary complications in abdominal surgeries: randomized controlled trial - Castro, Gabriel Isaac Pereira de [UNESP]; Castro, Renata Sayuri Ansai Pereira de [UNESP]; Lima, Rodrigo Moreira e; Santos, Bruna Nogueira dos; Navarro e Lima, Lais Helena [UNESP] (Elsevier, 2024)
Background: There is no consensus on the most effective strategy for Postoperative Pulmonary Complication (PPC) reduction. This study hypothesized that a Goal-Directed Fluid Therapy (GDFT) protocol of infusion of predetermined boluses reduces the occurrence of PPC in patients undergoing elective open abdominal surgeries when compared with Standard of Care (SOC) strategy. Methods: Randomized, prospective, controlled study, conducted from May 2012 to December 2014, with ASA I, II or III patients undergoing open abdominal surgeries, lasting at least 120 min, under general anesthesia, randomized into the SOC and the GDFT group. In the SOC, fluid administration was according to the anesthesiologist's discretion. In the GDFT, the intervention protocol, based on bolus infusion according to blood pressure and delta pulse pressure, was applied. Patients were postoperatively evaluated by an anesthesiologist blinded to the group allocation regarding PPC incidence, mortality, and Length of Hospital Stay (LOHS). Results: Forty-two patients in the SOC group and 43 in the GDFT group. Nineteen patients (45%) in the SOC and 6 in the GDFT (14%) had at least one PPC (p = 0.003). There was no difference in mortality or LOHS between the groups. Among the patients with PPC, four died (25%), compared to two deaths in patients without PPC (3%) (p = 0.001). The LOHS had a median of 14.5 days in the group with PPC and 9 days in the group without PPC (p = 0.001). Conclusion: The GDFT protocol resulted in a lower rate of PPC; however, the LOHS and mortality did not reduce.
Keywords: Anesthesia; Digestive system surgical procedures; Fluid therapy; Hemodynamic monitoring; Organism hydration status; Postoperative complications